Integración Externa en las Cadenas de Suministro Agroindustriales: Una Revisión al Estado del Arte - Ruiz Moreno, Andrés Felipe; Caicedo Otavo, Andrés Leonardo; Orjuela Castro, Javier Arturo (Ingeniería, 2015)
Supply Chain Integration (SCI) has been broadly taken into account due to its strategic importance; however, there are a few agri food supply chain studies. The purpose of this paper is to review the SCI focused on the external integration mechanisms impact on agri food supply chain performance. The results shows that external integration mechanisms most used have been information sharing and joint decision making, while efficiency has been frequently used as a performance indicators. The review identifies the need to assess several external integration mechanisms simultaneously on Supply Chain performance emphasizes on the importance to research in joint decision making mechanism, such as Vendor Managed Inventory (VMI) and Collaborative planning, forecasting, and replenishment (CPFR). For performance measurement, it is needed to include at least one indicator for each category (Efficiency, Flexibility, Responsiveness and Food Quality) of the Agri Food Supply Chain performance framework described, whereas for measuring Agri Food logistics performance is required further research on modes (process management) and means (resources) logistics.